Dīrāsātun ān-Nāẓārīyyātī āl-Idrākī Bīdāmjī Bārāmījī āt-Tāʿlīmī āt-Tāfāuʿlīyyī āl-Qāīmu āt-Tiknūlūjīyān fīī āt-Tāʿlīmī āl-Lughātī āl-ʿArābīyyātī - Mirantika, Mazi Septina; Aziz, Abdul; Utama, Wawan Kurnia; Furqan, Muhammad Ismail (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Digital transformation in the world of education has encouraged the use of interactive learning applications as a potential means to support foreign language acquisition, including Arabic. However, there has not been much research that examines the integration of these applications from a cognitive perspective theoretically. This research aims to deeply examine how interactive learning applications support Arabic language learning based on cognitive learning theories, such as information processing theory, cognitive constructivism, and cognitive load theory. The scope of the research includes the identification of cognitive features in the application, their relevance in Arabic language learning, and the potential for future development. The research method used is descriptive qualitative with literature study and content analysis techniques on academic literature such as articles, books, and other literature. Data sources are analyzed theoretically to reveal the contribution of interactive applications to the learning process from a cognitive perspective. The study results show that interactive applications support Arabic language learning through five main aspects: activation of initial cognitive attention, reinforcement of long-term memory through multimodality, knowledge construction, reduction of cognitive load, and enhancement of direct feedback. These findings prove that learning applications are not only technical aids but also pedagogical tools capable of enhancing the quality of language internalization. The conclusion of this study states that the integration of interactive learning applications in the context of the Arabic language is highly relevant and effective if based on cognitive principles. This research contributes scientifically to the development of technology-based Arabic language teaching strategies that are more adaptive to the mental processes of learners. Suggestions for future research include conducting further theoretical analyses on specific types of applications, exploring how different cognitive principles are represented in newer technologies, and expanding the literature review to include studies from diverse educational contexts and learner profiles.